Big data social media analytics for purchasing behaviour - Shayaa, Shahid; Ainin, Sulaiman; Piprani, Arsalan Zahid; Al-Garadi, Mohammed Ali; Ashraf, Muhammad Azeem (Science Publishing Corporation, 2018)
The social media is rich in data and of late its data have been used for various types of analytics. This paper examines the purchasing behavior and sentiments of social media users from Jan - 2015 to Dec - 2016. The purchasing behaviour of the users is categorized into five: buy car, buy house, buy computer, buy hand phone and going for holiday. The paper will also demonstrate the trend of each individual category. The results of the analysis would provide businesses information on the social media users' purchasing behavior, their sentiment thus allowing them to take more appropriate strategies to enhance their competitiveness.